The Relevance of the Vygotsky’s Sociocultural Approaches to Promote Interaction in EFL Classroom - Theophile Muhayimana (Yayasan Visi Intan Permata, 2017)
This paper that is a theoretical inquiry by design aimed at analyzing the importance and implications of the Vygotskian sociocultural approaches (VSA) on teaching and learning English as a foreign language (EFL). Scholarship indicated that EFL learners’ problems are tightly linked to the class culture that oftentimes involves teacher-centered instruction, rote learning, and restricted learner’s involvement and self-motivation in the learning process. It is the premise of this paper that revisiting the class culture and use the VSA will contribute a great deal to addressing some of communication and classroom interaction issues in EFL context. First, at the onset, the paper discussed the relevance of the framework to the teaching and learning of EFL. Second, the study delved into the literature that reviewed the four fundamental components of the framework that are tightly related to promoting language learning and classroom interaction. These concepts include social environment and use of tools vis-à-vis the learning and development process, scaffolding, and the notion of the zone of proximal development. Third, the paper looked into the implications of the VSA on enhancing interaction in EFL classroom that focused on knowledge about learners to better assist them, promotion of classroom discourse, and collaborative learning environment. Fourth, the conclusion underscored the paramount importance of the collaborative learning environment to sustain classroom interaction; that ending section also shed light on the limitations of the VSA and strategies to alleviate them.